The knowledge of contingent a priori truths, performatives and pragmatic inferences - Muhtaroğlu, Nazif. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2007., 2007)
Saul Kripke claims that there are contingent a priori truths. His argument for this claim depends on his account of naming. By assuming his account of naming, I try to improve his argument by adding two premises expressing the satisfaction of the success conditions of the naming activity and using that name. In characterizing the naming activity, I make use of the notion of performatives. In formulating a valid inference from premises to the conclusion, I appeal to the notion of pragmatic inferences. The gist of my argument for the a priority of Kripke’s contingent truths is that the knowledge of the mentioned two premises provides the correct grasp of the necessary and sufficient elements in order to grasp the proposition that is considered to be a contingent a priori truth. So this proposition is known just by grasping it without further investigation.
Keywords: A priori.